The Relationship of Workload with Burnout in Teachers - Rahma Afwina (Edumaspul: Jurnal Pendidikan, 2023)
This research is a quantitative research with correlation method. The purpose of this research is to see the correlation between workload and burnout. The hypothesis in this study is that there is a positive and significant correlation between workload and burnout. The population of this research is 60 teachers with a sample of 60 teachers. The technique used in determining the sample is the total sampling technique. Based on the results of the product moment correlation test, it can be seen that the significance value of the workload variable with burnout is 0.000 <0.05. This explains that there is a significant correlation between workload and teacher burnout. The Pearson correlation value obtained between workload and burnout is 0.483. This explains that the workload and burnout variables have a positive correlation with a fairly strong correlation coefficient. The value of the determinant coefficient obtained is equal to 23.4%. Based on the value of the determinant coefficient, it can be seen that the effect of workload on burnout is 23.4% and the remaining 76.6% is influenced by other factors.